JURIDICAL INSTRUMENTS OF CDM–CLEAN DEVELOPMENT MECHANISM–IN THE IMPLEMENTATION OF LEGAL RESERVE ENERGETIC PURPOSES IN BRAZIL - CATANEO, Pedro Fernando (Revista Brasileira de Engenharia de Biossistemas, 2012)
If the temperature of the Land was not for the effect greenhouse would be very low, esteem in the band of -32oC -23oC, and the life, as we know it, would have never appeared. The effect greenhouse is the physical process for which the presence of atmospheric gases makes with that the land keeps a temperature of bigger balance of the one than would have case they was absent. The global heating mentions the continuous increase to it and of long stated period of this temperature of balance. The presence of effect gases greenhouse is not problem, but yes its uncontrols, by making possible global heating in a level in which the global climate would be modified significantly. The risk of exaggerated global heating took countenance after the Industrial Revolution, to the measure that had the increase of the fossil fuel use in the means of production, raising very the levels of concentration of carbon dioxide (CO2), main gas it effect greenhouse, in the atmosphere. The Brazilian Forum of Climate Change has for objective the awareness and mobilization of the society for the quarrel and taking of position on the decurrent problems of the change of the climate for effect gases greenhouse, as well as on the Clean Development Mechanism (CDM) defined in article 12 of the Protocol of Kyoto to United Nations Framework Convention on Climate Change, ratified for the Brazilian National Congress by means of Legislative Decree nº 1, of 03 of February of 1994. The Brazilian Federal Constitution of 1988, in its article 225 standes out that all have right to the environment ecologicaly balanced, and essential to the quality of healthy life public easement, fitting to the government and the collective to defend it in the gift and to preserve it for the future. Thus, the question of the global heating leaves of being a question that desperte interest only in the environment professionals, ecologists and biologists, but for all society in which the man is enclosed. The question that if presents is not only of jurisprudence, that finds endorsement in the positive law, but yes, a survival question, of the man, that today dominates the Land, as well as of all the other forms of life, of which it is directly dependent. The Brazilian Forest Code establishes Legal Reserve as the area located in the interior of a country property, excepted of Permanent Preservation area, necessary to the sustainable use of the natural resources, to the conservation and whitewashing of the ecological processes, to the conservation of biodiversity and the shelter and protection of native fauna and flora. The Legal Reserve, in the ratios established in Law, has important function in this climatic process. Areas currently destined and regitered as Legal Reserve are lowermost, but, despite the high decurrent costs, they could be bigger, case the agricultural proprietors were sensetized how much to the collective benefits of its implantation. It considers in this work the implantation of areas of Legal Reserve, with financings and incentives, through legal instruments and politicians of the Clean Development Mechanism, form to promote the development sustainable of the property, the generation and/or maintenance of the income of the producers, as much for the Carbon commerce how much for the wooden production, mainly for energy ends, in way that the social function of the property, as foreseen in law, either reached.